Propuesta de diseño de una máquina semi industrial de apertura para la etapa de preproducción para la obtención de hilo a partir de fibra de alpaca - Sanchez Jimenez, Joan Jefferson (2021)
The present research thesis has the purpose of serving as contribution to promote the development of the processing of alpaca fiber in Peru when raising as proposal the design of a semi-industrial machine for the process of alpaca fiber opening, which has part within the preoperational stage in the production of yarn from alpaca fiber. This machine has an expected capacity of 2 kg/h of open fiber with a loss of 5%, giving a capacity 10 times higher compared to the 200g/h produced manually at the artisan level. As fundamental objective of the present research, the design of a semi-industrial machine for alpaca fiber opening process with motor of 1/2 HP must be completed. To achieve this, the diagnosis and evaluation of the opening process was carried out at an artisan level as well as at an industrial level to obtain characteristics that allow to complete the gap present between both levels of production. Then, the existing technology was identified to consider components and mechanisms accessible and offered in the national and international market. Later, the manual sketch was made establishing minimum and adequate criteria, thus justifying the technical characteristics of the machine. Furthermore, the computer-assisted design was achieved using the software Inventor 2018. Then, the materials and services of manufacture and assembly were selected, obtaining a total resulting cost of S/ 20,143 for the construction of the machine. This value is almost 86% cheaper compared to the cheapest industrial alternative in the international market (Fiber Picker-Opener machine from Ramella, Italy). Finally, the costs associated with maintenance and electrical consumption represent annually around 22% and 7% of the price of the machine, respectively; additionally, as a recommendation for the machine user, a single cost of S/2,485 is proposed, which allows the acquisition of personal protection equipment, tools, and implementation of Poka-Yoke devices.